Payment of sub-contractor at project pembinaan kuaters dan dewan tertutup bagi Jabatan Imigresen Malaysia di Bandar Baru Uda, Johor Bahru, Johor. / Muhammad Zikri Hafiz Ab. Aziz - Ab. Aziz, Muhammad Zikri Hafiz (2017)
GERBANG NUSAJAYA SDN BHD originated from humble beginning operating as a class ‘F’ contractor specializing in maintenance work since 1989. Since then, the company has grown into a dynamic civil engineering and construction company providing vital support to key industrial sectors such as infrastructure development, building, construction, telecommunication and M&E works.